ETHICAL CHALLENGES IN AI AND AUTOMATION IN MANAGEMENT: IMPLICATIONS FOR DECISION-MAKING, JOB DISPLACEMENT AND DATA PRIVACY - Aajaz Ahmad Hajam; Alphonsa S John (Universitas Efarina, 2024)
Artificial Intelligence (AI) and automation have rapidly become cornerstones in transforming management practices, streamlining operational efficiency, and enhancing decision-making capabilities across industries. However, these technologies present significant ethical challenges that cannot be overlooked. The core ethical concerns pertain to the transparency and fairness of AI-driven decision-making, the socio-economic effects of job displacement, and data privacy risks in the age of automation. This review article examines these ethical dilemmas through an extensive exploration of existing literature, identifying the key concerns and potential strategies for addressing them. Additionally, it proposes a research problem and objective focused on developing ethical frameworks to guide the integration of AI and automation into management. The conclusion emphasizes the need for collaborative efforts among stakeholders—corporations, governments, and civil society organizations—to ensure the responsible adoption of AI and automation technologies.